Analisis Perbaikan Drop Tegangan dengan Metode Pecah Beban pada Penyulang GNAP PT. PLN (Persero) ULP Plered - Nurjaman, Dede Furqon; Hakim Achmad Rifan; Taryana, Een; Hidayat, Wahyu (Department of Electrical Engineering, UNJANI, 2024)
The electricity demand continues to increase every year in line with advancing technology and society's dependence on electricity supply. The society's reliance on electricity drives the improvement of power quality by PLN, one of which is the enhancement of voltage quality. At PT. PLN (Persero) Unit Layanan Pelanggan (ULP) Plered, there is a distribution feeder with an end voltage that is still below the standard. In this study, an analysis of the system related to the improvement of voltage drop on the GNAP distribution feeder was conducted with the assistance of ETAP simulation. The voltage drop improvement was carried out using the load splitting method, which involves redistributing a portion of the load to another feeder. The obtained results show that the voltage drop on the GNAP feeder decreased from the initial 1.19 kV to 0.84 kV during daytime load and from 1.24 kV to 0.90 kV during nighttime load. The voltage loss also experienced a decrease from the initial 5.95% to 4.18% during daytime load and from 6.20% to 4.51% during nighttime load.